IMPLEMENTATION OF THE RIGHT TO EDUCATION FOR CHILDREN WITH DISABILITIES IN BANDA ACEH, ACEH PROVINCE, INDONESIA - Farissa, Farissa; Farsia, Lena (Student Journal of International Law, 2023)
This article examines the extent to which the Aceh government fulfils the right to education for children with disabilities and the challenges encountered in ensuring their access to education. The research methodology employed includes normative empirical approaches, incorporating both library and field research. The findings reveal that the government of Banda Aceh has demonstrated significant support for disabled children through the establishment of special schools, the implementation of regulations, provision of teacher training, allocation of education funds, and availability of autism therapy facilities. However, these schools remain insufficient in meeting the needs of disabled children. Additionally, in order to promote inclusivity, the Banda Aceh government should prioritize disability needs by focusing on equitable access to education, implementing anti-discrimination measures, enhancing educator training, increasing funding, and raising community awareness. Effective enforcement of regulations and extensive educational outreach emphasizing the importance of education for disabled children are crucial factors in this regard.